2010
DOI: 10.3989/scimar.2010.74s1143
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations in metallothionein concentration and subcellular distribution of metals in gills and digestive glands of the oyster <i>Crassostrea angulata</i>

Abstract: SUMMARY:The metallothionein levels and metal concentrations in whole body, digestive gland and gills of Crassostrea angulata were analyzed in field samples collected from the River Guadalquivir estuary over several years following a mining waste spill upstream. The subcellular distribution of metals was analyzed to determine the mechanisms involved in the detoxification process. The highest metallothionein levels were reported in the digestive gland shortly after the mining contamination event. In this organ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
1
1
1
Order By: Relevance
“…In aquatic invertebrates, MT play an important role in many physiological processes including homeostasis, protection against trace metals and oxidant damage, metabolic regulation, sequestration and/or redox control (Mao et al, 2012). Although several studies with bivalves have demonstrated positive correlations between MT measured in gills and metal content (Géret et al, 2002;Khati et al, 2012;Trombini et al, 2010), our results showed no relationship between MT and metal concentrations, except for Al. This lack of correlation has been previously reported for Mytilus galloprovincialis (Fernández et al, 2010) and also for mussel Mytilus edulis (Geffard et al, 2005).…”
Section: Discussioncontrasting
confidence: 84%
“…In aquatic invertebrates, MT play an important role in many physiological processes including homeostasis, protection against trace metals and oxidant damage, metabolic regulation, sequestration and/or redox control (Mao et al, 2012). Although several studies with bivalves have demonstrated positive correlations between MT measured in gills and metal content (Géret et al, 2002;Khati et al, 2012;Trombini et al, 2010), our results showed no relationship between MT and metal concentrations, except for Al. This lack of correlation has been previously reported for Mytilus galloprovincialis (Fernández et al, 2010) and also for mussel Mytilus edulis (Geffard et al, 2005).…”
Section: Discussioncontrasting
confidence: 84%
“…In this study, MT content in oysters from XZ was significantly higher than that from other sites. Several studies have found that MT content had positive correlations with metal concentrations in bivalves (Trombini et al, 2010;Khati et al, 2012). Furthermore, Cd, Cu and Zn were also regarded as an inducer of MT (Viarengo et al, 1997;Marigomez et al, 2002), which was consistent with the high levels of Cd, Cu and Zn at XZ site.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, among the established mechanisms of lead toxicity is its ability to induce oxidative stress following an overproduction of ROS. An imbalance between antioxidants and pro-oxidants is a result of this toxicity and causing an alteration in redox status, lipids peroxidation and protein oxidations [39][40]. Malondialdehyde (MDA) constitutes the final products of lipid peroxidation indicating the degradation of lipids; it is therefore used as a good biomarker of lipid damage in aquatic organisms [4].…”
Section: Discussionmentioning
confidence: 99%